The effect of low shear force on the virulence potential of Yersinia pestis: new aspects that space-like growth conditions and the final frontier can teach us about a formidable pathogen - Rosenzweig, Jason A. (Frontiers in Cellular and Infection Microbiology, 2012)
Manned space exploration has created a need to evaluate the effects of space-like stress (SLS) on pathogenic and opportunistic microbes. Interestingly, several Gram-negative enteric pathogens, e.g., Salmonella enterica serovar Typhimurium, have revealed a transient hyper-virulent phenotype following simulated microgravity (SMG) or actual space flight exposures. We have explored the virulence potential of Yersinia pestis KIM/D27 (YP) following exposure to mechanical low shear forces associated with SMG. Our experimental results demonstrated that SMG-grown YP was decreased in its induced HeLa cell cytotoxicity, suggesting that SMG somehow compromises T3SS functions. This was confirmed by an actual reduced amount of effector protein production and secretion through the T3SS injectisome. Also, SMG-grown YP proliferated less than their NG-grown counterparts did during an 8-h macrophage infection. Presently, we are evaluating the influence of SMG on various KIM/D27 mutant strains to further understanding of our initial phenomenology described above. Taken together, characterizing YP grown under the low shear forces of SMG can provide new insights into its pathogenesis and potentially uncover new targets that could be exploited for the development of novel antimicrobials as well as potential live-attenuated vaccines.